Implementasi Program Bantuan Langsung Tunai Dana Desa Tahun 2020 pada Masyarakat Desa Terdampak Covid-19 di Desa Kresek - Alya Nurayu (Epistemik: Indonesian Journal of Social and Political Science, 2022)
The global pandemic caused by the spread of the covid-19 virus outbreak has an impact on a very significant economic decline for Indonesia. The Indonesian government has issued a policy to stimulate the economy of the affected communities by launching the Direct Cash Assistance program sourced from village funds or what can be called BLT-DD. This study aims to analyze the implementation of the Village Fund Direct Cash Assistance Program Policy by examining how the BLT-DD Program is implemented in Kresek Village, Kresek District. The theory used in this study uses the theory of public policy implementation proposed by Van Meter and Van Horn, which includes: Policy Standards and Objectives, Resources, Communications, Implementor Characteristics, Implementor Dispositions, Economic, Social Conditions, and Politics. The method of writing in this study uses a descriptive method with a qualitative research approach. The results of this study indicate that the implementation of the village fund direct cash assistance program in Kresek village has not been going well. This can be seen from the theoretical analysis knife which shows that the standards and objectives of the existing policies are urgent with limited time so that many stages of the BLT-DD program distribution are not carried out, the utilization of resources is not maximal, the communication is minimal, the characteristics and disposition of the Kresek village government as the implementor who is not optimal and the economic and social conditions of the residents of Kresek Village have decreased, accompanied by the atmosphere of the Kresek Village Pilkades preparation process.